Estrogens Play a Critical Role in Stress-Related Gastrointestinal Dysfunction in a Spontaneous Model of Disorders of Gut–Brain Interaction - Alison Accarie; Joran Toth; Lucas Wauters; Ricard Farré; Jan Tack; Tim Vanuytsel (Cells, 2022)
Background: Disorders of the gut–brain interaction (DGBI), such as irritable bowel syndrome and functional dyspepsia, are more prevalent in women than in men, with a ratio of 2:1. Furthermore, stressful life events have been reported as one of the triggers for symptoms in DGBI patients. Methods: Here, we studied the effect of an early-life stressor (maternal separation (MS)) on jejunal and colonic alterations, including colonic sensitivity and immune cells infiltration and activation in a validated spontaneous model of DGBI (BBDP-N), and investigated the involvement of β-estradiol on stress-worsened intestinal alterations. Results: We found that maternal separation exacerbated colonic sensitivity and mast cell and eosinophil infiltration and activation in females only. Ovariectomy partially rescued the stress phenotype by decreasing colonic sensitivity, which was restored by β-estradiol injections and did not impact immune cells infiltration and activation. Stressed males exposed to β-estradiol demonstrated similar intestinal alterations as MS females. Conclusion: Estrogen plays a direct critical role in colonic hypersensitivity in a spontaneous animal model of DGBI, while for immune activation, estrogen seems to be involved in the first step of their recruitment and activation. Our data point towards a complex interaction between stress and β-estradiol in DGBI.